2020
DOI: 10.1021/jacs.0c05362
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective Copper-Catalyzed Azidation of Benzylic C–H Bonds

Abstract: Site selectivity represents a key challenge for non-directed C−H functionalization, even when the C−H bond is intrinsically reactive. Here, we report a copper-catalyzed method for benzylic C−H azidation of diverse molecules. Experimental and density functional theory studies suggest the benzyl radical reacts with a Cu II -azide species via a radical-polar crossover pathway. Comparison of this method with other C−H azidation methods highlights its unique site selectivity, and conversions of the benzyl azide pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 47 publications
(84 reference statements)
10
106
1
Order By: Relevance
“…The remarkably different enantioselectivities between the neutral Box L1 and the anionic CN‐Box L4 triggered us to investigate the insight of these ligands. Considering the versatile bridging modes of azide in copper complexes, neutral Box (e.g., L1 ) coordinated monomeric (L1)Cu II azide species could simultaneously dimerize to give an azide bridged (L1)Cu II dimer, which was supported by our DFT calculation at the ω B97X‐D level of theory (Δ G =−13.6 kcal mol −1 , see Figure S2) [3g, 12] …”
Section: Methodssupporting
confidence: 64%
See 2 more Smart Citations
“…The remarkably different enantioselectivities between the neutral Box L1 and the anionic CN‐Box L4 triggered us to investigate the insight of these ligands. Considering the versatile bridging modes of azide in copper complexes, neutral Box (e.g., L1 ) coordinated monomeric (L1)Cu II azide species could simultaneously dimerize to give an azide bridged (L1)Cu II dimer, which was supported by our DFT calculation at the ω B97X‐D level of theory (Δ G =−13.6 kcal mol −1 , see Figure S2) [3g, 12] …”
Section: Methodssupporting
confidence: 64%
“…Radical azidation represents a powerful tool for the synthesis of alkylazides [3d–g, 6] . However, nearly all the present protocols lead to the racemic targets, [7] which results from notorious difficulty as the following reasons: (1) the ready generation of the azidyl radical could result in the undesired side reactions, which would depletes the desired radical coupling with carbon‐centered radicals; [8] (2) transition metal‐catalyzed radical azidation reactions were demonstrated as efficient tools for the alkylazide synthesis, [3g, 6, 7, 9] where the C‐N 3 bonds are generated from an outer sphere pathway with carbon radical attacking at terminal N 3 atom (Scheme 1 A). Thus, the relatively far away of reaction site to catalyst chiral center make enantioselective radical azido‐transfer even more challenging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stahl and group came up with another such important transformation involving site-selective copper-catalyzed azidation of benzylic CÀ H bonds. [38] Although the authors have demonstrated a wide substrate scope for benzylic CÀ H azidation, most of the examples are demonstrated employing alkylarenes. Only a few substrates exemplify benzylic CÀ H azidation of diarylmethanes (Scheme 22).…”
Section: Cà X Bond Formation (X = Heteroatom)mentioning
confidence: 99%
“…For this reason, several efforts have been demonstrated for specific sp 3 C−H azidation (one such example is included above; Scheme ). Stahl and group came up with another such important transformation involving site‐selective copper‐catalyzed azidation of benzylic C−H bonds . Although the authors have demonstrated a wide substrate scope for benzylic C−H azidation, most of the examples are demonstrated employing alkylarenes.…”
Section: Metal‐catalyzed Benzylic C‐h Functionalization Of Diarylmethmentioning
confidence: 99%